VUCA and other analytics in business resilience - Singh, Deepmala; Sood, Kiran; Kautish, Sandeep, 1981-; Grima, Simon (Emerald studies in finance, insurance, and risk management ;, 2024)
Company executives need strategic flexibility in VUCA to maintain an advantage alongside business analytics, helping them achieve a competitive edge by providing timely insights, optimizing business processes, and generating growth and innovation opportunities. Strategic questions arise as firms begin their business analytics programmes, and VUCA and Other Analytics in Business Resilience brings together specialists from different disciplines and continents to provide answers. The chapters discuss organizational justice, sustainable HR, machine learning, and more, providing future roadmaps to minimise disruption during occurrences like the COVID-19-related worldwide catastrophe and the ramifications for managers and policymakers. Emerald Studies in Finance, Insurance, And Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.